Prognostic Model of Surgical Treatment of Severe Mitral Regurgitation at Mitral Valve Prolapse - Mokhnatyi, S. I.; Dovgan, O. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
The article presents a single-center experience of surgical treatment of patients with severe mitral regurgitation(MR) caused by mitral valve prolapse (MVP). The study is based on long-term results of reconstructive interventions on the mitral valve (MV) of the UCCC of the Ministry of Health of Ukraine. The purpose of this work is to determine the factors that influence the long-term results of surgical treatment of MR in prolapse of the mitral valve leaflets. Material and methods.From January 1, 2011, to January 1, 2018, 146 patients with severe MR were operated on the basis of the UCCC, which was conditioned by the prolapse of mitral valve leaflets. Results.Long-term results were analyzed in 95.2% of patients. The average postoperative follow-up period was 39.7 ± 19.8 months. The overall mortality rate was 1.4%. Freedom from moderate and severe MR in the remote postoperative period decreased to 94.2%, compared to the early postoperative period. Residual MR was absent in 17 (12.4%) patients. In 76 (55.5%) patients trivial MR was detected, in 36 (26.3%) there was a mild MR, in 3 (2.2%) a moderate MR. In 5 (3.6%) patients, a severe MR was detected during the observation. Using statistical methods, it was found that the anatomical variant of MVP influences the prognosis of treatment results in the long postoperative period with worse results in the group with isolated prolapse of the anterior leaflet. Also, the dependence of the results on the applied surgical techniques with better results in annuloplication using the annuloplasty rings and in the application of resection of the posterior mitral leaflet. On the basis of statistics, a prognostic model for the evaluation of MV repair results in the distant period was developed. The height of coaptation of mitral leaflets was determined as one of the indicators for predicting the results of surgical treatment of MR with MVP. Conclusions: 1. In most cases, a successful mitral valve repair is possible with the MVP. 2. A good immediate result does not mean keeping it in the long term. 3. The long-term results of MV reconstruction depend on the anatomical variant of the MVP, with worse results in patients with isolated prolapse of the anterior mitral leaflet. 4. The result of MV repair depends on the surgical techniques used, with better results when using the annuloplasty rings and resection of the posterior mitral leaflet. 5. The height of the coaptation of the MV leaflets is an indicator that allows predicting the outcome of surgical treatment in the long postoperative period.